Models In Keeping Ancestral Heritage Significance (Zien Journal of Social Sciences and Humanities, 2022)
This article discusses the methods of making manuscript copies of unique manuscripts and historical documents of spiritual heritage, its importance and necessity in the preservation of historical objects today. Typically, professional manuscript of manuscripts and historical documents began to develop over the next 5 years to be included in the museum’s exposition. The article discusses in detail the current requirements for the development of this direction and the initial successful results achieved.